2014
DOI: 10.1186/bf03352230
|View full text |Cite
|
Sign up to set email alerts
|

Secular variation and reversals in a composite 2.5 km thick lava section in central Western Iceland

Abstract: The direction and intensity of primary remanence has been measured in oriented specimens from 367 lava flows of Late Miocene age in Western Iceland. The lavas which were sampled in 8 overlapping profiles, were generally good material for paleomagnetic measurements. In a 2500-m composite section, at least 15 reversals of polarity and several excursions are recorded. The mean remanence direction and other overall paleomagnetic parameters for the present collection of lavas are similar to those found elsewhere in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…4), indicating absence of more than one directionally distinct high-coercivity components. This behavior is also dominant in lavas from other surveys in Iceland (e.g., Kristjansson and Johannesson 1999 , Fig. 3).…”
Section: Paleomagnetism-methods and Sample Characteristicsmentioning
confidence: 65%
See 1 more Smart Citation
“…4), indicating absence of more than one directionally distinct high-coercivity components. This behavior is also dominant in lavas from other surveys in Iceland (e.g., Kristjansson and Johannesson 1999 , Fig. 3).…”
Section: Paleomagnetism-methods and Sample Characteristicsmentioning
confidence: 65%
“…Some of these lavas might be more appropriately named "flow units" or "compound flows" (cf. Watkins and Walker 1977;Kristjansson and Johannesson 1999). This serial correlation is quite common in the Miocene to Quaternary lava pile in Iceland (see Kristjansson et al 1980, Section 5.2;Kristjansson et al 2003).…”
Section: Serial Correlationmentioning
confidence: 92%
“…However, no In the stippled area, basement rocks are less than 0.8 Ma old, and we also indicate the position of the 10 Ma isochron (Saemundsson, 1986). The numbers refer to publications where the composite surveys are reported, as follows: (1) Watkins and Walker (1977); (2) Helgason (1982), Bleil et al (1982); (3) Kristjansson et al (1995); (4) McDougall et al (1976b) and Kristjansson and Gudmundsson (2005); (5) Helgason and Duncan (2001); (6) Saemundsson et al (1980); (7) Kristjansson et al (1992); (8) Kristjansson et al (2004); (9) Doell (1972), Kristjansson et al (1988), Eiriksson et al (1990); (10) McDougall et al (1984); (11) Kristjansson and Johannesson (1996); (12) Kristjansson et al (2003); (13) ; (14) Kristjansson and Johannesson (1999); (15) Kristjansson et al (1980); (16) Kristjansson et al (1991); (17) Kristjansson and Gudmundsson (2001). certain correlations between distant parts of the country, using e.g. particular geomagnetic epochs or extensive clastic horizons, have been found so far.…”
Section: Stratigraphy: Work Since 1972mentioning
confidence: 90%
“…The result of these processes is to reduce the magnetizatioñ 3-6 A m -1 Johnson, 1991, 1993a;Smith and Banerjee, 1986). For comparison, a recent study of subaerial Icelandic basalts found a maximum magnetization of 16.2 A m -1 (Kristjansson and Johanesson, 1999).…”
Section: Terrestrial Rock Magnetizationmentioning
confidence: 99%